The Antidiabetic Potential of Quercetin: Underlying Mechanisms - Eid, Hoda M; Haddad, Pierre S (Current medicinal chemistry, 2017)
The dramatic increase in modern lifestyle diseases such as cancer, cardiovascular diseases and diabetes has renewed researchers' interest to explore nature as a source of novel therapeutic agents. Flavonoids are a large group of polyphenols that are widely present in the human diet. They have shown promising therapeutic activities against a wide variety of ailments. One of the most widely distributed and most extensively studied flavonoid is the flavonol quercetin. Its powerful antioxidant and anti-inflammatory activities are well documented and are thought to play a role in treating and protecting against diseases including diabetes, cancer, neurodegenerative and cardiovascular diseases. The purpose of this review is to shed light on quercetin therapeutic potential as an antidiabetic agent. Quercetin was reported to interact with many molecular targets in small intestine, pancreas, skeletal muscle, adipose tissue and liver to control whole-body glucose homeostasis. Mechanisms of action of quercetin are pleiotropic and involve the inhibition of intestinal glucose absorption, insulin secretory and insulin-sensitizing activities as well as improved glucose utilization in peripheral tissues. Initial studies suggested poor bioavailability of quercetin. However, recent reports have shown that quercetin was detected in the plasma after food or supplements consumption and has a long half-life in human body. Despite the wealth of in vitro and in vivo results supporting the antidiabetic potential of quercetin, its efficacy in diabetic human subjects is yet to be explored.